A proto-oncogene BCL6 is up-regulated in the bone marrow microenvironment in multiple myeloma cells - Hideshima, Teru (American Society of Hematology, 2010)
Constitutive B-cell lymphoma 6 (Bcl-6) expression was undetectable in multiple myeloma (MM) cell lines, except U266 cells. However, it was up-regulated by coculture with bone marrow (BM) stromal cell-culture supernatant (SCCS). Bcl-6 expression in patient MM cells in the BM was positive. Anti–interleukin-6 (IL-6)–neutralizing antibody significantly blocked SCCS-induced Bcl-6 in MM cells. Indeed, IL-6 strongly triggered Bcl-6 expression in MM cells, whereas Janus kinase inhibitor and STAT3 siRNA down-regulated Bcl-6. Tumor necrosis factor-α (TNF-α) also triggered Bcl-6, but independently of STAT3, whereas IκB kinaseβ inhibitor down-regulated TNF-α–induced Bcl-6, indicating that the canonical nuclear factor-κB pathway mediates TNF-α–induced Bcl-6 expression. Importantly, down-regulation of Bcl-6 by shRNA significantly inhibited MM cell growth in the presence of SCCS. Our results therefore suggest that Bcl-6 expression in MM cells is modulated, at least in part, via Janus kinase/STAT3 and canonical nuclear factor-κB pathways and that targeting Bcl-6, either directly or via these cascades, inhibits MM cell growth in the BM milieu.